Electronic patient-reported outcome measures using mobile health technology in rheumatology: A scoping review. - Jaclyn Shelton (Public Library of Science (PLoS), 2021)
Objective This scoping review aims to characterize the current literature on electronic patient-reported outcome measures (ePROMs) in rheumatology and assess the feasibility and utility of ePROMs and mobile health technology in the management of rheumatic disease. Introduction Patient-reported outcome measures (PROMs) are commonly used in rheumatology as they are important markers of disease activity and overall function, encourage shared decision-making, and are associated with high rates of patient satisfaction. With the widespread use of mobile devices, there is increasing interest in the use of mobile health technology to collect electronic PROMs (ePROM). Inclusion criteria All primary studies that involve the collection of ePROMs using mobile devices by individuals with a rheumatic disease were included. Articles were excluded if ePROMs were measured during clinic appointments. Methods A scoping review was performed using Medline, Embase, PsycINFO, and CINAHL with index terms and key words related to "patient-reported outcome measures", "rheumatic diseases", and "mobile health technology". Results A total of 462 records were identified after duplicates were removed. Of the 70 studies selected for review, 43% were conference proceedings and 57% were journal articles, with the majority published in 2016 or later. Inflammatory arthritis was the most common rheumatic disease studied. Generic ePROMs were used over three times more often than disease-specific ePROMs. A total of 39 (56%) studies directly evaluated the feasibility of ePROMs in clinical practice, 19 (27%) were clinical trials that used ePROMs as study endpoints, 9 (13%) were focus groups or surveys on smartphone application development, and 3 (4%) did not fit into one defined category. Conclusion The use of ePROMs in rheumatology is a growing area of research and shows significant utility in clinical practice, particularly in inflammatory arthritis. Further research is needed to better characterize the feasibility of ePROMs in rheumatology and their impact on patient outcomes.